2016
DOI: 10.1037/a0039140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job insecurity on employee health complaints: A within-person analysis of the explanatory role of threats to the manifest and latent benefits of work.

Abstract: The current study contributes to the literature on job insecurity by highlighting threat to the benefits of work as an explanation of the effect of job insecurity on health complaints. Building on the latent deprivation model, we predicted that threats to both manifest (i.e., financial income) and latent benefits of work (i.e., collective purpose, social contacts, status, time structure, activity) mediate the relationships from job insecurity to subsequent mental and physical health complaints. In addition, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 39 publications
2
71
1
6
Order By: Relevance
“…One of the most accurate approaches when establishing an empirical hypothesis is based on the studies that have aimed at adapting the deprivation model (Jahoda, 1982) to job insecurity. It has been empirically shown that the expectation of losing latent working functions has similar effects on health as those of the real loss that occurs with unemployment (Vander Elst et al, 2016). Thus, the fact that the impact on mental health caused by unemployment is comparable to the impact resulting from a job insecurity situation is supported.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One of the most accurate approaches when establishing an empirical hypothesis is based on the studies that have aimed at adapting the deprivation model (Jahoda, 1982) to job insecurity. It has been empirically shown that the expectation of losing latent working functions has similar effects on health as those of the real loss that occurs with unemployment (Vander Elst et al, 2016). Thus, the fact that the impact on mental health caused by unemployment is comparable to the impact resulting from a job insecurity situation is supported.…”
Section: Discussionmentioning
confidence: 96%
“…Scientific literature often addresses the impact of job insecurity on workers' mental health (Vander Elst, Näswall, Bernhard-Oettel, De Witte, & Sverke, 2016), but there is currently no systematic review that focuses specifically and deeply on this relationship. While the previous meta-analyses (Cheng & Chan, 2008;Sverke et al, 2002) carried out a global diagnosis of the consequences of job insecurity, this study establishes three ground-breaking and priority objectives: (1) to clarify the direct relationship between job insecurity and psychological health, (2) to update the results of the existing reference meta-analyses with the recent research findings of the last decade, (3) study if job insecurity affects people from countries in the north and south of Europe in a different way, based on the differences in labour market and social circumstances of each territory, and (4) to evaluate the different types of job insecurity scales to determine their appropriate characteristics for a good evaluation of the phenomenon.…”
Section: The Current Studymentioning
confidence: 99%
“…Results from the present study overall corroborate findings from previous cross-sectional [ 17 22 ] studies, as well as prospective studies that have established the association between job insecurity and impaired SRH both in the mid-and long-term [ 23 26 , 29 ]. It is evident that time plays an important role in this relationship: findings from cross-sectional [ 17 22 ] and prospective studies, with time windows between 1 and 12 years, have convincingly shown an association [ 26 , 27 , 29 ]. The present study is partly in line with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived probability of losing the actual job (eg, job insecurity) threatens the satisfaction of these needs and can negatively impact health and well-being. Research indeed shows that threats to the various benefits of work mediate the association between job insecurity and subsequent mental and physical health complaints (17,18). A related logic stems from Self-Determination Theory (19), which states that the satisfaction of three basic psychological needs is crucial for individuals to flourish, namely, autonomy, belongingness, and relatedness.…”
Section: On the Scarring Effects Of Job Insecurity (And How They Can mentioning
confidence: 99%